2001
DOI: 10.1128/aac.45.7.2144-2146.2001
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Mechanism of Human Immunodeficiency Virus Type 1 Reverse Transcriptase Resistance to Stavudine

Abstract: We have found a close correlation between viral stavudine (d4T) resistance and resistance to d4T-triphosphate at the human immunodeficiency virus type 1 reverse transcriptase (RT) level. RT from site-directed mutants with 69S-XX codon insertions and/or conventional zidovudine resistance mutations seems to be involved in an ATP-dependent resistance mechanism analogous to pyrophosphorolysis, whereas the mechanism for RT with the Q151M or V75T mutation appears to be independent of added ATP for reducing binding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
43
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 26 publications
6
43
0
2
Order By: Relevance
“…This makes sense, considering the intrinsic relationship between the two processes and would suggest that a mutant that mediates resistance by removal would not show dramatic reductions in the incorporation of an analog. In support of this hypothesis, studies on RT AZTR , which appears to confer resistance by removing chain-terminating AZTMP (34,36,37,40) and D4TMP (39,68,69), have shown very little or no reduction in the incorporation of AZTMP (25,35). Consistent with previous reports suggesting that AZT resistance mutations cause resistance by increasing the rate of dNMP removal a role in resistance to abacavir.…”
Section: Role For the Hydrophobic Nature Of Cbvtp's Ribose Ring Insupporting
confidence: 73%
See 2 more Smart Citations
“…This makes sense, considering the intrinsic relationship between the two processes and would suggest that a mutant that mediates resistance by removal would not show dramatic reductions in the incorporation of an analog. In support of this hypothesis, studies on RT AZTR , which appears to confer resistance by removing chain-terminating AZTMP (34,36,37,40) and D4TMP (39,68,69), have shown very little or no reduction in the incorporation of AZTMP (25,35). Consistent with previous reports suggesting that AZT resistance mutations cause resistance by increasing the rate of dNMP removal a role in resistance to abacavir.…”
Section: Role For the Hydrophobic Nature Of Cbvtp's Ribose Ring Insupporting
confidence: 73%
“…Interestingly, RT Q151M also showed an elevated rate of ATP-mediated removal of dGMP; however, it was slightly slower than RT WT at removing CBVMP. This suggests that removal may play a role in Q151M-mediated resistance to some compounds, although studies have suggested removal to be unimportant in its resistance to AZT (40) or D4T (68).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…However, the level of resistance needed to have a clinical effect against d4T is small (1.4-fold) (32), and it has been reported that mutations causing resistance to AZT can cause cross-resistance to d4T (12,19,23,32,35). At high dNTP concentrations, which favor the formation of the ternary complex and inhibit the excision reaction, SSGR/T215Y excises d4TMP to a much greater extent than wild-type RT.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to suggest that AZT resistance mutations cause low-level resistance to stavudine (d4T), which can be important clinically (19,23,32). We used the excision-extension assay to examine the ability of wild-type HIV-1 RT and the RT variants to excise d4TMP.…”
Section: Vol 78 2004 Effects Of the ⌬67 Complex In Hiv-1 Rt On Nrtimentioning
confidence: 99%